Concentrations of psychoactive substances in blood samples from non‐fatal and fatal opioid overdoses. Issue 10 (13th May 2022) - Edvardsen, Hilde Marie Erøy; Aamodt, Carl; Bogstrand, Stig Tore; Krajci, Peter; Vindenes, Vigdis; Rognli, Eline Borger
Abstract : Aim: The primary aim was to compare concentrations of psychoactive substances in blood in non‐fatal and fatal opioid overdoses. The secondary aim was to assess the concentration levels of naloxone in blood in non‐fatal overdoses and the association between naloxone findings and concomitantly detected drugs. Method Design: Case‐control study. Setting: Norway. Fatal overdoses from 2017 and non‐fatal overdoses from February 2018 to September 2019. Cases: Thirty‐one non‐fatal and 160 fatal opioid overdose cases. Data from the non‐fatal overdoses were collected from hospital records and blood samples, and data from the fatal overdoses were collected from autopsy reports. Concentrations of psychoactive substances (including ethanol) in blood samples were collected at the time of hospital admission for the non‐fatal overdoses and during autopsy for the fatal overdoses. Results: The median number of different substances detected was four for fatal and five for non‐fatal overdoses. The fatal overdoses had higher pooled concentrations of opioids (188 vs 57.2 ng/mL, P < .001), benzodiazepines (5467 vs 2051 ng/mL, P = .005) and amphetamines (581 vs 121 ng/mL, P < .001) than the non‐fatal overdoses. A linear relationship between naloxone and concomitant pooled opioid concentrations was found (95% confidence interval = 0.002‐0.135, P < .05). Conclusion: The total load of drug concentrations was associated with the fatal outcome of an overdose, while the number of drugs used, to a lesser extent, differentiated between those who survived and those who died from an overdose. Higher opioid concentrations were associated with treatment with higher naloxone doses.